1990
DOI: 10.1111/j.1532-5415.1990.tb03470.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Rates in Nursing Home Residents with Dementia

Abstract: Although Special Care Units (SCUs) have recently gained attention as appropriate places for caring for institutionalized patients with dementia, few studies have evaluated their effectiveness. This pilot study focused primarily on one aspect of patient care, the possible prevention of acute hospitalization. Because transfer from nursing home to the acute hospital can be a traumatic experience for patients with dementia, important services that SCUs might provide include those preventive strategies aimed at red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…A greater global cognitive impairment in the SCU group was found in 10 studies with large [33,38,39,42], moderate [20,28,36] and small effect sizes [21,34] or significant p values [43]. In contrast, 1 study showed an increased cognitive impairment with a large effect size in a limited number of participants [35], and 1 study showed a moderate effect size in a younger n-SCU patient group [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater global cognitive impairment in the SCU group was found in 10 studies with large [33,38,39,42], moderate [20,28,36] and small effect sizes [21,34] or significant p values [43]. In contrast, 1 study showed an increased cognitive impairment with a large effect size in a limited number of participants [35], and 1 study showed a moderate effect size in a younger n-SCU patient group [9].…”
Section: Resultsmentioning
confidence: 99%
“…self-care, for the n-SCU group with large [38], small [33] and very small [20,31] effect sizes or p values [43]. …”
Section: Resultsmentioning
confidence: 99%
“…This is troublesome, because there are well‐reported differences between NHs with and without SCUs on a variety of measures. Of studies with control groups from the same NH, some did not appear to acknowledge or control for the differences between SCU and non‐SCU residents 22,70 . The design of this study attempted to overcome some of these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Studies focused on how care is provided have shown some differences, but these have often been inconsistent. [19][20][21][22][23] Further complicating the issue, problems in study design, especially control group selection, make findings difficult to interpret and limit knowledge on ''true'' SCU effects.…”
mentioning
confidence: 99%
“…Our results also showed progressive worsening of subjective health and increased mortality in RH residents versus those in NHs. For those who are medically unstable or with poor physical functioning, NHs may help them avoid hospitalization and both reduce and prevent the functional deterioration that frequently follows hospitalization [26]. NH nursing homes, RH residential care homes.…”
Section: The Emphasis On Community-based Care and Social Factors In Imentioning
confidence: 99%